DEVELOPMENT OF RATIONAL EMOTIVE BEHAVIOR THERAPY BASED ON RELIGIOUS VALUES IN IMPROVING STUDENT DISCIPLINE - SITI WAHYUNINGSIH SAPUTRI; IQBAL BAFADAL; MIRA MARETA (Universitas Islam Negeri Mataram, 2023)
The behavior of students in the world of education is always developing in all aspects. This form of development leads not only to positive things, but also to negative things. This research was motivated by the high level of disciplinary violations that occurred at MTS NW Pringgasela, Pringgasela District, East Lombok Regency, especially students in grades VIII and IX. The purpose of this study is to develop rational emotive behavior therapy counseling based on religious values in improving discipline. The method used is Research and Development where researchers first create the concept of rational emotive behavior therapy based on religious values through Qur'anic verses surah An-Nisa and wisdom stories about the Art of Living a Life Full of Meaning in improving discipline that is tested on a limited basis. The results showed that with rational emotive behavior therapy counseling based on religious values through Qur'anic verses surah An-Nisa and wisdom stories about the art of living a meaningful life in improving discipline was effectively used in helping to improve student discipline